Lojistik köylerin Türkiye'nin dış ticaretine etkisi - Bastık, Nimet (My University, 2020)
Lojistik köyleri, farklı bölümleri barındıran, koordinasyon ve iĢ birliğini sağlamak için bu farklı bölümler arasında uyum oluĢturmak için politikalar oluĢturan bir lojistik kümedir. Lojistik köyler ile yük dağıtımı ile ilgili tüm faaliyetler ülkeler arası seviyeden kıtalararası düzeye eriĢmektedir. Bu köylerin üzerine gerekli altyapı çalıĢmaları yapıldığında ise hem istihdamı arttırmakta hem de ekonomik ve çevresel sürdürülebilirliğe katkıda bulunmaktadır. Lojistik köyleri tedarik zincirinde sadece malzeme taĢıma ve depolama için altyapı sağlamaz aynı zamanda amaca yönelik tüm sistemlere de gerekli hizmeti sunarlar. Tüm lojistik köyleri kurulduğu alana göre farklı amaçlar barındırsa da temelinde daha verimli ve etkili bir yük taĢıma sistemi sunmaktır. Kuruldukları bölgelerin ekonomilerine göre farklılaĢan lojistik köyler yapabileceklerini de yine bu bölgenin dinamizmine göre belirler. Genel olarak geliĢmekte olan ekonomilerde kalkınmaya, geliĢmiĢ ekonomilerde ise sürdürülebilirlik ve rekabet gücüne olan katkısı bu lojistik köylerin tüm dünyada örneklerinin olmasına katkı sağlamıĢtır. Türkiye‟deki örnekler üzerine yoğunlaĢmıĢ olan bu çalıĢma farklı bölgelerde farklı amaçlarla kurulmuĢ olsa da dıĢ ticarete olan etkisi yadsınamayacak örnekleri bir araya getirmiĢtir. Türkiye‟de aktif olarak hizmetlerini sürdüren lojistik köylerini dıĢ ticarete etkisini ölçek adına yapılan bu çalıĢmada 6 tanesi devlet eliyle bir tanesi de özel bir Ģirket tarafından yapılan 7 lojistik köyünün SWOT analizi yapılmıĢtır. Yapılan analiz dıĢ ticarete etkisini görmek amacıyla olduğundan SWOT içerisindeki unsurlar dıĢ ticaret bağlamında incelenmiĢtir. Jeopolitik konumu sebebiyle dıĢ ticarete etki etmesi beklentisiyle açılan köylerin yeterli altyapı, tesis imkanı, istihdam kalitesi ve ekipman yetersizliği sebebiyle dıĢ ticarete yeterli etkiyi yapamadığı çalıĢma sonuçları arasındadır. Lojistik köy, lojistik merkezi, dıĢ ticaret ii

Logistics villages are a logistic cluster that hosts different departments and creates policies to create harmony between these different departments to ensure coordination and cooperation. All activities related to logistics villages and cargo distribution reach from inter-country level to intercontinental level. When the necessary infrastructure works are carried out on these villages, it both increases employment and contributes to economic and environmental sustainability. Logistics villages not only provide infrastructure for material transportation and storage in the supply chain, but also provide the necessary service for all purpose-oriented systems. Although all logistics villages have different purposes according to the area they are established, their basis is to offer a more efficient and effective freight transport system. The logistics villages that differ according to the economies of the regions where they are established determine what they can build according to the dynamism of this region. In general, its contribution to development in developing economies and to sustainability and competitiveness in developed economies has contributed to these logistics villages being examples of all over the world. This study, which concentrates on samples with different purposes in different regions in Turkey established though undeniable impact on the foreign trade has brought together examples. SWOT analysis of logistic villages is made for to observe the impact of foreign trade. The logistic villages are selected among “operational status” and six of them is established by public and one of them is established by a private company. Since the analysis made is in order to see its effect on foreign trade, the elements in SWOT are examined in the context of foreign trade. It is among the results of the study that villages, which were opened with the expectation that they would affect foreign trade due to their geopolitical location, could not make enough impact on foreign trade due to the lack of sufficient infrastructure, facility facilities, employment quality and equipment. Logistic village, logistic center, foreign trade
Keywords: Finance; Lojistik köy Logistic village; Maliye